O4.1. AEROBIC EXERCISE DOSE DETERMINES THE COGNITIVE GAIN IN FIRST-EPISODE SCHIZOPHRENIA, SO HOW DO WE ENCOURAGE SUFFICIENT EXERCISE?. (18th May 2020) - Nuechterlein, Keith; Ventura, Joseph; McEwen, Sarah; Subotnik, Kenneth; Turner, Luana; Boucher, Michael; Distler, Margaret; Casaus, Laurie
Abstract: Background: Increasing evidence supports the benefits of regular aerobic exercise for cognition and functioning in schizophrenia. The extent to which these gains are dependent on the amount of aerobic exercise completed remains unclear, although variability in adherence to intended exercise regiments is evident. Furthermore, strategies for encouraging regular exercise sessions in schizophrenia are only starting to be explored. Methods: In a randomized controlled trial with 47 first-episode patients with schizophrenia, we contrasted six months of Cognitive Training & Exercise (CT&E) with Cognitive Training (CT) alone. The computerized cognitive training using PositScience BrainHQ and SocialVille programs was provided to all participants, four hours/week at the UCLA clinic for six months. The CT&E group also participated in total body circuit training exercises, with a goal of completing 150 minutes/week. Two of the aerobic exercise sessions were held at the clinic, while the other two were to be completed at home. Intensity of exercise was titrated individually with a heart rate monitor, targeting 60–80% of heart rate reserve. Several incentive strategies to encourage regular exercise were incorporated. Cognitive gain was measured by the MATRICS Consensus Cognitive Battery (MCCB), while the Global Assessment Scale: Role was used to index work/school functioning gain. Results: Both groups showed cognitive and work/school functioning gains, but the improvements were three times as large when aerobic exercise was added to cognitive training (for MCCB Overall Composite, Mixed Model F = 7.19, p<.02, effect size Cohen's f = 0.43). The magnitude of cognitive improvement among the CT&E patients differed substantially, so predictors of the cognitive gain were sought. The CT&E patients completed a mean of 85% of their in-clinic aerobic exercise sessions, compared to an average of 39% of their home exercise sessions. Patients who completed a higher overall proportion of their exercise sessions showed the largest cognitive gains (r=0.51, p=.03). This relationship was particularly apparent for completion of home exercise sessions (r=0.54, p=.02). Thus, aerobic exercise showed a dose-response relationship to cognitive improvement. Paying $5 for each completed home exercise session was helpful, but variability in exercise adherence remained. Assigning points for completing the most exercise sessions in the desired heart rate zone and awarding a monthly winner also aided exercise adherence. Dividing patients into two groups that competed monthly for most exercise sessions in the heart rate zone was also motivating, but group competition had mixed results. Pilot work with smartphone reminder systems is underway. Discussion: The addition of systematic aerobic exercise to cognitive training resulted in substantially more cognitive and functional gain than cognitive training alone. The magnitude of cognitive improvement was clearly related to the amount of regular exercise completed. Several strategies were employed to boost the frequency of exercise, particularly the number of exercise sessions completed outside of clinic group exercise sessions. Development of systematic incentive strategies to encourage regular aerobic exercise will be critical to successful dissemination of exercise programs as part of the treatment of schizophrenia.